The Influence Of Habit, Hedonic Motivation, Social Influence, And Digital Financial Literacy On DecisionsUse Of Qris By Students - Agung Prakoso; Ahmad Rifa’I; Maulana Agung (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to identify and analyze the influence of habits, hedonic motivation, social influence, and digital financial literacy on the decision to use QRIS by students at three private universities in Bandar Lampung City. The method used in this research is a survey with data collection techniques through questionnaires distributed to 100 students using QRIS. The data collected was analyzed using the multiple linear regression method to test the influence of each variable on the decision to use QRIS. The research results show that hedonic motivation and digital financial literacy have a significant positive influence on the decision to use QRIS, while habitual and social influences show a positive but not significant influence. Simultaneously, all independent variables have a significant influence on the decision to use QRIS. These findings provide insight that understanding digital financial literacy and hedonic motivation play an important role in driving decisions to use QRIS among students. We hope that this research can become a reference for developing policies and strategies to expand the application of QRIS among students.